Development and usage of computer expert systems in agriculture - Bardaie, Mohd. Zohadie (Agricultural Institute of Malaysia, 1989)
An expert system is a computer software system that is able to provide advice in a particular subject area equal in quality to that which could be provided by an acknow- ledged human expert- Expert sys- tems do not generate new know- ledge. What they do is provide access to existing expert knowledge. How- ever, that knowledge may well be new to the user of the computerised expert system, and herein lies its benefit.